NITROGEN, PHOSPHORUS, AND POTASSIUM RANGE OF VERMICOMPOST USING EISENIA FETIDA AND PERIONYX EXCAVATUS - SHARMILA K J; GOMATHY B; DIVYA BALAMANI P; KALPANA N; NANDHA KUMAR P (Innovare Journal of Agricultural Sciences, 2019)
The aim of the presentation is to produce vermicomposting from organic kitchen solid wastes using two types of earthworms such as Eisenia fetida and Perionyx excavatus and check the nitrogen, phosphorus, and potassium level between E. fetida and P. excavatus. This study examines the potential of the E. fetida and P. excavatus in the vermicompost of kitchen waste. As kitchen waste is rich in organic material. Physical and biochemical parameters were analyzed during the period of 60 days. Pre-decomposition is 15 days and subsequent vermicomposting is 60 days indicates, the rule of these species of vermitechnology increase was found in all the parameters such as total nitrogen (%), available phosphorus (%), and exchangeable potassium (%) while a decrease was found in pH and carbon-to-nitrogen ratio in E. fetida as the timing of vermicomposting increased from 0 days to 60 days.